TINGKAT KEPATUHAN KONSUMSI TABLET TAMBAH DARAH (TTD) TERHADAP KEJADIAN ANEMIA REMAJA PUTRI DI SMP PANGUDI LUHUR 1 YOGYAKARTA - Shofiatul Ma’rifah, Diana; Susanti, Isne; Oktavia3, Eka (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Adolescent famale are a group of teenagers who are prone to suffering from anemia. According to WHO in 2021, the prevalence of anemia in women aged 15-49 years reached 29.9%, while in Indonesia cases of iron deficiency anemia in adolescent girls were 22.7%. Based on the results of the Preliminary Study of the Yogyakarta City Health Office in 2024, as many as 18 health centers in the coverage area of the Yogyakarta City Health Office, the highest cases of anemia in adolescent girls were in the Umbulharjo 2 Health Center, which was 43.27%. Based on the Preliminary Study of the Umbulharjo 2 Health Center, Pangudi Luhur 1 Yogyakarta Middle School ranked first with the highest number of cases of anemia in adolescent girls at the school level, which was 47.22%. This study aims to determine the level of compliance with the consumption of Iron Supplement Tablets (TTD) against the incidence of anemia in adolescent girls at Pangudi Luhur 1 Yogyakarta Middle School. This study uses a correlational analytical research type with a cross-sectional research design. The sampling technique used purposive sampling technique of 68 female students. The data used are primary and secondary data. The instruments used are questionnaires and digital hemoque hb checks. Univariate data analysis techniques. Data were analyzed by conducting Chi square analysis tests. The results of the validity test of this study showed a value of r table <0.5. The results of the study from 68 female adolescent respondents who were compliant with the consumption of iron tablets were 44 female students (64.7%) and non-compliant were 24 female students (35.3%). Female adolescents who did not experience anemia were 44 female students (64.7%), mild anemia were 15 female students (22.1%), moderate anemia were 9 female students (13.2%), and no female adolescents experienced severe anemia. The conclusion of this study is expected to contribute to the development of knowledge about the factors that influence the incidence of anemia in female adolescents.